2007
DOI: 10.1158/1535-7163.mct-07-0310
|View full text |Cite
|
Sign up to set email alerts
|

Under normoxia, 2-deoxy-d-glucose elicits cell death in select tumor types not by inhibition of glycolysis but by interfering with N-linked glycosylation

Abstract: In tumor cells growing under hypoxia, inhibiting glycolysis with 2-deoxy-D-glucose (2-DG) leads to cell death, whereas under normoxic conditions cells similarly treated survive. Surprisingly, here we find that 2-DG is toxic in select tumor cell lines growing under normal oxygen tension. In contrast, a more potent glycolytic inhibitor, 2-fluorodeoxy-D-glucose, shows little or no toxicity in these cell types, indicating that a mechanism other than inhibition of glycolysis is responsible for their sensitivity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
275
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 229 publications
(291 citation statements)
references
References 38 publications
14
275
0
2
Order By: Relevance
“…It has been reported that in cancer phenotypes in which low-dose treatment with 2-DG (<4 mmol/L) induces cell death under normoxia, 2-DG acts through inhibition of Nlinked glycosylation (12,14). D-Mannose has been shown to reverse both the growth inhibitory and cytotoxic effects associated with inhibition of N-linked glycosylation but cannot reverse the cytotoxic effects triggered by inhibition of glycolysis (25,26).…”
Section: -Dg Induces Growth Inhibition and Cell Death In All Cells Umentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that in cancer phenotypes in which low-dose treatment with 2-DG (<4 mmol/L) induces cell death under normoxia, 2-DG acts through inhibition of Nlinked glycosylation (12,14). D-Mannose has been shown to reverse both the growth inhibitory and cytotoxic effects associated with inhibition of N-linked glycosylation but cannot reverse the cytotoxic effects triggered by inhibition of glycolysis (25,26).…”
Section: -Dg Induces Growth Inhibition and Cell Death In All Cells Umentioning
confidence: 99%
“…2-DG can induce cell growth arrest and cell death by inhibiting 2 key glycolytic enzymes, hexokinase and phosphoglucose isomerase (PGI; ref. 12). Following facilitated diffusion into cells through glucose transporters, 2-DG is converted to 2-DG-6-phosphate by hexokinase, but unlike glucose-6-phosphate, 2-DG-6-phosphate cannot be further metabolized by PGI, and its accumulation inhibits the glycolytic pathway (13).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When proteins cannot be glycosylated, misfolded proteins accumulate, and the unfolded protein response is engaged. Indeed, ER stress, rather than energetic stress, may be the leading cause of cell death on treatment of some tumor cells with antiglycolytics such as 2-DG (Kurtoglu et al, 2007).…”
Section: Sensing Glucose Deprivationmentioning
confidence: 99%